Utilization and satisfaction of volunteer law enforcement officers in the office of the American sheriff: an exploratory nationwide study. (2nd September 2016) - Wolf, Ross; Holmes, Stephen T.; Jones, Carol
Abstract : Many government organizations utilize volunteers to enhance services, and volunteers have been used in law enforcement agencies for a variety of functions. However, volunteers in American policing are a largely under-studied part of the criminal justice system. This current paper examines the utilization of volunteer reserves, auxiliaries, and special deputies in the office of the American sheriff. The article also examines the perceived organizational characteristics of those agencies that treat volunteers the same as regular full-time sworn deputies by allowing them full power of arrest and the authority to carry a weapon on and off duty. The results generally show that volunteer deputies that are treated the same as their full-time counterparts in regard to authority and responsibility are generally more satisfied with their role within the organization and report greater satisfaction with the organization in terms of communication, leadership, and professionalism.